2021
DOI: 10.1002/mc.23283
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6 and IL‐8, secreted by myofibroblasts in the tumor microenvironment, activate HES1 to expand the cancer stem cell population in early colorectal tumor

Abstract: Interaction between a tumor and its microenvironment is important for tumor initiation and progression. Cancer stem cells (CSCs) within the tumor interact with a microenvironmental niche that controls their maintenance and differentiation. We investigated the CSC‐promoting effect of factors released from myofibroblasts into the microenvironment of early colorectal cancer tumors and its molecular mechanism. By messenger RNA microarray analysis, expression of HES1, a Notch signaling target, significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…As a previous study indicated that hypoxic tumor microenvironment (TME) could result in a significant metabolic reprogramming for Tregs (which are especially susceptible to hypoxic metabolic signaling) and subsequently lead to an abnormal survival and proliferation of these cells [ 64 ]. Except this, it was found that certain inflammatory cytokines like IL-6, which was significantly higher in TME and peripheral blood of CRC patients [ 65 , 66 ], could impact the migration capacity of Tregs to the lesion [ 67 ]. Take into account these studies, we speculate that the cases with blank Tregs would have a special TME or significant high IL-6 that could prevent the infiltrating or kill Tregs; however, more studies are still needed to validate this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…As a previous study indicated that hypoxic tumor microenvironment (TME) could result in a significant metabolic reprogramming for Tregs (which are especially susceptible to hypoxic metabolic signaling) and subsequently lead to an abnormal survival and proliferation of these cells [ 64 ]. Except this, it was found that certain inflammatory cytokines like IL-6, which was significantly higher in TME and peripheral blood of CRC patients [ 65 , 66 ], could impact the migration capacity of Tregs to the lesion [ 67 ]. Take into account these studies, we speculate that the cases with blank Tregs would have a special TME or significant high IL-6 that could prevent the infiltrating or kill Tregs; however, more studies are still needed to validate this speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal cancer appears to be particularly sensitive to inflammation (20,21). Inflammation can trigger and accelerate the development of cancer, leading to the formation of malignant tumors (22). IL-6 is a key regulator of CRC tumorigenesis, tumor growth, metastasis, and chemotherapy resistance, and it mainly activates the ERK, AKT, JAK2/STAT3 pathway and Twist initiating a vicious loop securing the EMT phenotype (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal cancer seems to be particularly sensitive to inflammation [19,20]. Inflammation can trigger and accelerate the development of cancer, leading to the formation of malignant tumors [21]. IL-6 is a key regulator of prostate tumorigenesis, tumor growth, metastasis and chemotherapy resistance [22].…”
Section: Discussionmentioning
confidence: 99%